Morphology and flow fields of three-dimensional dunes, Rio Paraná, Argentina: Results from simultaneous multibeam echo sounding and acoustic Doppler current profiling - Parsons, Daniel R. (2005)
[1] Most past studies of river dune dynamics have concentrated on two-dimensional (2-D) bed forms, with constant heights and straight crest lines transverse to the flow, and their associated turbulent flow structure. This morphological simplification imposes inherent limitations on the interpretation and understanding of dune form and flow dynamics in natural channels, where dune form is predominantly three-dimensional. For example, studies over 2-D forms neglect the significant influence that lateral flows and secondary circulation may have on the flow structure and thus dune morphology. This paper details a field study of a swath of 3-D dunes in the Rio Paraná, Argentina. A large (0.35 km wide, 1.2 km long) area of dunes was surveyed using a multibeam echo sounder (MBES) that provided high-resolution 3-D detail of the river bed. Simultaneous with the MBES survey, 3-D flow information was obtained with an acoustic Doppler current profiler (ADCP), revealing a complicated pattern of dune morphology and associated flow structure within the swath. Dune three-dimensionality appears intimately connected to the morphology of the upstream dune, with changes in crest line curvature and crest line bifurcations/junctions significantly influencing the downstream dune form. Dunes with lobe or saddle-shaped crest lines were found to have larger, more structured regions of vertical velocity with smaller separation zones than more 2-D straight-crested dunes. These results represent the first integrated study of 3-D dune form and mean flow structure from the field and show several similarities to recent laboratory models of flow over 3-D dunes. Copyright 2005 by the American Geophysical Union.